ANALISIS TINGKAT KEBUGARAN JASMANI PADA SISWA EKSTRAKURIKULER FUTSAL DI SMPN 13 BANJARBARU - Muhamad Ikhsan Ashari; Ramadhan Arifin; Akhmad Amirudin (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
Futsal requires a significant level of physical fitness to perform at its best. The objective of this study is to assess the degree of physical fitness among futsal extracurricular students at SMPN 13 Banjarbaru. This study employs a descriptive methodology utilizing a quantitative approach. The study's population consisted of 14 futsal extracurricular students from SMPN 13 Banjarbaru. The research sample consisted of eight futsal extracurricular students from SMPN 13 Banjarbaru, chosen using the purposive selection technique. We gathered the data using the Indonesian Physical Fitness Test for individuals aged 13-16 years. This test consists of the following components: a 50-meter sprint, a 60-second body lift hang, a 60-second sitting bar, an upright jump, and a 1000-meter run. The findings indicated that the physical fitness level of futsal extracurricular students at SMPN 13 Banjarbaru was comparatively inadequate. There are no students in the excellent category, which accounts for 0% of the total. Similarly, there are no students in the good category, which accounts for 0% of the total. There are 3 students in the moderate category, accounting for 37.5% of the total. Additionally, there are 5 students in the less category, representing 62.5% of the total. Lastly, there are no students in the extremely poor category. The level of physical fitness among the futsal extracurricular students at SMPN 13 Banjarbaru is relatively inadequate. Additional rigorous physical fitness training is required to enhance student performance in futsal.